2021
DOI: 10.3390/polym13071171
|View full text |Cite
|
Sign up to set email alerts
|

Physicomechanical Properties of Rice Husk/Coco Peat Reinforced Acrylonitrile Butadiene Styrene Blend Composites

Abstract: Utilizing agro-waste material such as rice husk (RH) and coco peat (CP) reinforced with thermoplastic resin to produce low-cost green composites is a fascinating discovery. In this study, the effectiveness of these blended biocomposites was evaluated for their physical, mechanical, and thermal properties. Initially, the samples were fabricated by using a combination of melt blend internal mixer and injection molding techniques. Increasing in RH content increased the coupons density. However, it reduced the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Both composites had a more hydrophobic resistance compared to epoxy resin. Furthermore, Norhasnan et al [ 62 ] evaluated a hybridized RH/coco peat reinforced ABS, which showed reduced water-resistance biocomposite structures. Figure 1 shows the moisture absorption behaviour of the RH/CP reinforced ABS, and a maximum water kinetic behaviour for 20 wt % of coco peat composite composition was found, due to the higher hydrophilicity of the coco peat particle.…”
Section: Water Diffusion Behavior Of Rh Compositesmentioning
confidence: 99%
“…Both composites had a more hydrophobic resistance compared to epoxy resin. Furthermore, Norhasnan et al [ 62 ] evaluated a hybridized RH/coco peat reinforced ABS, which showed reduced water-resistance biocomposite structures. Figure 1 shows the moisture absorption behaviour of the RH/CP reinforced ABS, and a maximum water kinetic behaviour for 20 wt % of coco peat composite composition was found, due to the higher hydrophilicity of the coco peat particle.…”
Section: Water Diffusion Behavior Of Rh Compositesmentioning
confidence: 99%
“…Table 3 and Table 4 show the chemical composition, as well as the mechanical and physical properties of the natural and E-glass fibers. Additionally, the effects of using this material has a positive impact because it is low-cost, reusable, biodegradable, environmentally friendly, and sustainable [ 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, under certain circumstances, the properties of single FRP composites might fail to meet the desired level of characteristics. Accordingly, scientists began to incorporate more than one type of reinforcing fibers in a single matrix, forming hybrid FRP composites [ 7 , 8 , 9 ]. The synergistic effects of hybridization between more than one fiber could overcome the drawbacks of single FRP composites.…”
Section: Introductionmentioning
confidence: 99%